Contribution of Parenting Parenting in Children's Character Building (Comparative Study of Duren and Sruwen Villages, Tengaran District, Semarang Regency) - Solihin Solihin; Khoiruddin Nasution; Ma’mun Efendi Nur (Journal Research of Social Science, Economics, and Management, 2022)
Parents are the main role models for their children, guiding, directing good behavior to their children so that they have good behavior. The aims of this study were 1) to analyze how the parenting style used in the formation of children's character in Duren Village and Sruwen Village; 2) To find out how the differences in parenting patterns in the formation of children's character in Duren Village and Sruwen Village; 3) To find out how the construction of parenting for children in Duren Village and Sruwen Village and its relevance in facing the current millennial generation. The researcher uses a mixed type of research (mixed methodology). The results of the study are: 1) The parenting style of parents in Duren Village is authoritative parenting, namely parents who apply democratic parenting have clear rules and expectations, and parenting in Sruwen Village is authoritarian parenting where parents are the center, namely the center of everything. the words/words, as well as the will of the parents, are used as a benchmark that must be obeyed by the child; 2) Parents in Duren Village in shaping children's character through behavior that is very effective in directing children, while parenting in Sruwen Village in caring for their children is more concerned with the wishes of parents, children are supervised quite closely, parents always keep their distance from children; 3) The construction of democratic parenting in Duren Village will give birth to an assertive personality, which is the ideal type, so that not many people are weak. Meanwhile, the construction of authoritarian and permissive parenting in Sruwen Village can make children feel unloved, isolated, and even hated by their parents.